Remembrance to László Huzián (1923-1996) - Bozsik, András (Acta Agraria Debreceniensis, 2010)
László Huzián was a determining personality of the higher education of Hungarian crop protection more precisely that of the agricultural entomology. Training of the scientific and extension specialists of Hungarian agricultural entomology from 1960 till 1983 would have been unimaginable without him. He was the builder of the agricultural entomology school established by Gusztáv Adolf Manninger, the developer of the training’s essential and organisational standard, who sacrificed his life’s work for developing the crop protection. He found, characterized many pests (E.g. Scrobipalpa ocellatella, Lixus scabricollis, Tanymecus palliatus, Mesagroicus obscurus) new for the Hungarian fauna and worked out a control technology against them. It is important to mention his activity in creating the forecasting of the big field crop animal pests mainly that of the sugar beet pests. One top of his educational work was the wonderful manual „Agricultural Entomology” written with Sándor Bognár in 1979. László Szalay-Marzsó said of this book that it was impossible to write a better one. He has been right. The magnificent crop protection library and the unique richness and accuracy of the animal demonstration material (slides, pictures, preparates, showcases, etc.) established at the Gödöllő University of Agriculture can be thanked to his extraordinary systematizing mentality and tireless efforts.